Rural livelihoods and natural resource sustainability : a case study of two communities on Chiloé Island : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Rural Development at Massey University, New Zealand - Bannister Hepp, Alan (Massey University, 2005)
This research examines the relationship between livelihood strategies of rural communities in Chile and local environmental sustainability. It determines livelihood options adopted by local communities and identifies their impact on the surrounding environment. Two case studies are presented using the sustainable livelihood approach as a framework to describe the livelihood strategies of two rural communities in Chiloé Island. Environmental sustainability is investigated using elements and concepts of the FESLM (Framework for Evaluating Sustainable Land Management) approach and of agroecosystem analysis. Both communities were selected because of their location close to extensive areas of native forests. One community is relatively isolated, has a “Huilliche” ethnic tradition, with a predominance of subsistence activities; the other is closer to markets and their livelihoods are primarily derived from farming-forestry systems. Data for the study was collected from in-depth semi-structured interviews and key informant interviews with local leaders, relevant local government staff, NGOs, and community members. For the examined cases, results suggest that rural subsistence communities are highly diversified, using their resources in a non-sustainable way; generating livelihood strategies that fail to improve their social, economic and environmental conditions. Low productivity soils, steep slopes, and depleted fragile forest ecosystems create a complex natural resource base. The main causes for the community economic problems are the lack of road networks and markets to sell products to. Organisations in charge of development interventions are aware of the situation but find it difficult to start a sustainable development process, mostly due to a lack of human capital in the communities, notably education, organisational skills, and technology adoption. Future development interventions should tackle the issues that constrain development in these communities, consider rural communities’ context-specific characteristics, value local culture and tradition, facilitate to build social and human capital, ensure integrated management of natural resources, and assist with markets for existing and value-added products produced by local households.
Keywords: sustainable rural development; livelihood strategies; environmental sustainability; Chile; SLA (sustainable livelihood approach); 440406 Rural community development